Screening for cardiac disease in potential recruits to the British Army. Issue 3 (20th August 2015) - Cox, Andrew T; Cameron-Smith, M; Folkes, F; Sharma, S; Boos, C
Abstract : The British Army screens potential recruits for disease, including cardiovascular disease, at the pre-employment medical assessment in the Army Selection Centres. The epidemiology of cardiovascular disease in the Armed Forces coupled with the high physical demand placed on the cardiovascular system, often in remote locations make screening desirable. This is particularly pertinent as servicemen and women die from cardiovascular disease each year. To evaluate this particular screening system it is essential to understand the aim of the system, how it is designed and how screening systems in general are evaluated. The efficacy of a screening test is quantified using the measurements of sensitivity, specificity and likelihood ratios. These measurements are defined and the pitfalls associated with evaluating a screening system are described. The different screening tests used to identify cardiac disease and their individual strengths and weaknesses, are illustrated. Finally the article reviews the previous British Army recruit cardiac screening system, that used a stereotyped history and physical examination and the newer system that replaced it, which includes the incorporation of the 12-lead ECG and on site echocardiography in individuals revealing abnormalities on history, examination or ECG.